2001
DOI: 10.1097/00007890-200101150-00009
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized and Prospective Study Comparing Treatment With High-Dose Intravenous Immunoglobulin With Monoclonal Antibodies for Rescue of Kidney Grafts With Steroid-Resistant Rejection

Abstract: Should the favorable result presented in this report be confirmed in larger number of patients, IVIg could become the preferable choice of rejection treatment for steroid-resistant rejection because of a complete absence of the unwanted side effects commonly associated with OKT3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 24 publications
0
70
0
5
Order By: Relevance
“…Pretreatment with IVIg results in reductions of anti-HLA antibodies and is effective in treatment of allograft rejection episodes (10,28,29). The high-dose IVIg protocol that was developed at Cedars-Sinai evolved from re-ported efficacy with other inflammatory disorders (e.g., Kawasaki disease) (14).…”
Section: Clinical Use Of Ivig In Kidney Transplantationmentioning
confidence: 99%
“…Pretreatment with IVIg results in reductions of anti-HLA antibodies and is effective in treatment of allograft rejection episodes (10,28,29). The high-dose IVIg protocol that was developed at Cedars-Sinai evolved from re-ported efficacy with other inflammatory disorders (e.g., Kawasaki disease) (14).…”
Section: Clinical Use Of Ivig In Kidney Transplantationmentioning
confidence: 99%
“…In addition, IVIG are effective in the treatment of steroid-resistant acute rejections after kidney transplantation (5,6). It is unknown whether IVIG are effective as prophylaxis for acute rejection after organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies showed that IVIG was as effective as OKT3 in reversing steroidresistant acute rejection episodes (Casadei et al, 2001). In the setting of antibody-mediated rejection, IVIG has been shown to be beneficial when used in conjunction with plasmapheresis and/or rituximab (Lefaucher et al, 2009;Shehata et al, 2010).…”
Section: Applicationsmentioning
confidence: 99%